Analisis Kedalaman Sumber Anomali Gravitasi menggunakan Spectral Statistical Technique di daerah Godean Yogyakarta - Muhammad Faizal Zakaria (Jurnal Fisika FLUX, 2021)
Depth analysis of the gravity anomaly source using Spectral Statistical Technique has been carried out in the Godean area, Yogyakarta. This research was conducted to determine the depth of the formation in the study area. This study used 56 gravity acquisition points spread over 2 lines  along 12 km east-west direction. Depth analysis is carried out from the Complete Bouguer Anomaly profile. Spectral Statistical Technique is used as a method of determining depth by calculating the slope of the graph Ln (PS) vs k. The results of these calculations are obtained slope of 2 types of anomalies, namely deep anomalies and shallow anomalies. The deep anomaly has a slope of -9704, while the shallow anomaly has a slope of -279. The depth of the anomalous source in the study area has a value of 770 m for deep anomalies interpreted as Nanggulan formations, and 22 m for shallow anomalies interpreted as the Merapi Muda Volcano Deposition.